DISTRIBUSI SPASIAL DAN LUAS KERUSAKAN HUTAN MANGROVEDI WILAYAH PESISIR KWANDANG KABUPATEN GORONTALO UTARA PROVINSI GORONTALO - Dewi Wahyuni K. Baderan (GeoEco, 2017)
Mangrove forest is one form of vegetation that has characteristics that can grow and thrive in tidal areas and muddy. The mangrove ecosystem is a unique ecosystem because it has a variety of functions well it functions ecologically very complex which is as spawning (spawning ground), nursery grounds, and feeding ground various types of marine life and has the economic function of which mangrove fruit can be processed into alternative food sources instead of rice. Mangrove in this region have experienced over the functions that are not controlled and the impact on changes in the area of mangroves and loss of flora and fauna in this location. This study aims to assess the spatial distribution and the extensive destruction of mangrove forests in the coastal region Kwandang Gorontalo province. The analytical method used is a map-based spatial analysis the preparation of thematic maps; image interpretation, landform map, the map use / landuse, land units maps, vegetation maps, maps destruction of mangrove forests, and mangrove forest vegetation index maps. This study found that the level of damage of mangrove forests in the coastal areasKwandang period of 10 years to reach 63%, where changes in forest area of mangroves is caused by pengalihfungsian mangrove areas into embankment land, farms, plantations, settlements, and harbor even based on the analysis of land units in 2010 found that the area that was the area of mangrove vegetation has now changed its designation into a pond with an area of 395.10 hectares, moor or agricultural land area of 179.43 hectares, 156.19 hectares of scrub area, covering an area of 92.24 hectares of rice fields, settlements of 36 , 53 hectares, the port area of 1,904 hectares, and the open land area of 23.89 hectares.Keywords: ecosystems, mangroves, damage, spatial